2010
DOI: 10.1136/bmj.c3691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium supplements on risk of myocardial infarction and cardiovascular events: meta-analysis

Abstract: Objective To investigate whether calcium supplements increase the risk of cardiovascular events.Design Patient level and trial level meta-analyses.Data sources Medline, Embase, and Cochrane Central Register of Controlled Trials (1966-March 2010), reference lists of meta-analyses of calcium supplements, and two clinical trial registries. Initial searches were carried out in November 2007, with electronic database searches repeated in March 2010.Study selection Eligible studies were randomised, placebo controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

28
692
10
32

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 987 publications
(762 citation statements)
references
References 56 publications
(104 reference statements)
28
692
10
32
Order By: Relevance
“…(7)(8)(9) Calcium supplements also have been associated with increased cardiovascular event rates in a randomized, controlled trial in older women (10) and subsequent meta-analysis. (11) The mechanism of the association between calcium metabolism and vascular disease is unknown. The process of vascular calcification is thought to be similar to bone formation, (12,13) and since calcium supplements increase bone mineral density (BMD), (14,15) they also may increase vascular calcification.…”
Section: Introductionmentioning
confidence: 99%
“…(7)(8)(9) Calcium supplements also have been associated with increased cardiovascular event rates in a randomized, controlled trial in older women (10) and subsequent meta-analysis. (11) The mechanism of the association between calcium metabolism and vascular disease is unknown. The process of vascular calcification is thought to be similar to bone formation, (12,13) and since calcium supplements increase bone mineral density (BMD), (14,15) they also may increase vascular calcification.…”
Section: Introductionmentioning
confidence: 99%
“…In their analyses of calcium monotherapy and MI, the authors identified only one trial (with four MIs) published after our metaanalysis, (2) explaining the similarity of results (Lewis, (2) and when self-reports are excluded (RR 1.33 [1.03-1.73]). (5) In their analyses of calcium plus vitamin D, the authors included two trials not in our meta-analysis, (3) one trial with one MI, and the second a trial by Larsen and colleagues.…”
mentioning
confidence: 98%
“…Their conclusion is at odds with that of our meta-analyses, which reported that calcium increased the risk of myocardial infarction (MI) and possibly stroke in men and women together. (2,3) There are important differences between approaches to the meta-analyses. In the current article and previously, the authors suggest that including men and self-reported events may have explained the increased risk of MI from calcium.…”
mentioning
confidence: 99%
See 2 more Smart Citations